The teaching and learning of L2 English intonation in a distance education environment - Estebas Vilaplana, Eva (Linguistica (Ljubljana), 2017)
The teaching of intonation to learners of a second language (L2) tends to be an arduous and often neglected task even in specialized phonetic classes. This difficulty generally increases in a distance learning environment where students have to approach prosodic issues in an autonomous way. This paper tests the advantages and disadvantages of using a new model to teach English intonation to Spanish speakers in a self-tuition context, called TL_ToBI (Teaching and Learning ToBI), and compares the benefits of this proposal with the traditional methodologies. Two groups of Spanish students of English phonetics in a distance learning environment took part in this study. Each group was trained with a different methodology: 1) the British School of intonation and 2) TL_ToBI, which involves an adaptation of the ToBI conventions for teaching purposes. The intonation of four sentence types was assessed: declarative, yes-no question, wh-question, and imperative, produced both with neutral and marked readings. The results showed that those speakers trained with TL_ToBI produced more native-like intonation patterns than those instructed with the other model. These findings suggest that a system based on tonal targets and their association to the metrical structure has more benefits for the acquisition of the L2 prosody in a distance learning setting.
Keywords: angleščina; britanska šola; English; intonacija; španski govorci; TL_ToBI; tuji jeziki; učenje na daljavo